Rancang Bangun Alat Pengisian Laddle Nikel Matte Otomatis dengan Sensor HC- SR 04 dan Buzzer Menggunakan Mikrokontroller Atmega - Zukri, Wahyu Apriansyah; Rigel, Rigel; Antarissubhi, Antarissubhi; Adriani, Adriani (MASALIQ, 2023)
As we already know that the majority of work accidents in mining in Indonesia are fatal. Advances in technology and shifting work practices can increase the number of work accidents due to a lack of understanding of workers at work locations. As a result, we need tools that can reduce the number of work accidents and the number of deaths due to work accidents. Microcontrollers are now very widely used because they are very useful and very helpful in solving problems. Microcontrollers are widely used in everyday life, for example traffic lights. Therefore, the author has the idea to create an automatic tool based on the Atmega microcontroller using the Research and Development (R&D) method. The design of this tool uses the Arduino Atmega microcontroller as a controller and the HC-SR04 sensor to detect the fill level in the laddle and a servo motor to open and close the filling valve. With this tool, it can overcome the problems of the mining industry in the form of human labor in very dangerous areas in the mining industry. The results of this study are that this tool is capable of filling, lifting, carrying and pouring matte nickel laddles automatically.